Avaliação da experiência do orçamento participativo numa cidade média: o caso de Jaboticabal - SP - Viglio, José Eduardo (2004)
The strength of the county power since 1988 made possible a greater autonomy by the counties in local range. Parallely in some counties came out mechanism of institutional inovation which aim the common citizen to take part into the decisions around the municipal budget. These expiriences denominated Participatory Budget (PB) are developed nowadays in more than hundred brazilian counties. This assignment aimed to describe and interpretate the mainly characteristics from Participatory Budget developed in the county of Jaboticabal from 1999 2002; topics related to Coordination, the framework and dynamic of the Participatory instaces and the relation of this process to the municipal budget. This assignment also proposes to understand the factors related to the PB conclusion from 2003, based on variable explanation present on the literature. To fulfill the proposal of this assignment, surveys were made with the coordination rep and other members from the admnistrative area, collection and documentation analises. The results proved that the PB Coordination was directly tied to Admnistration and not to an organism associated to a Participatory process and despite of occupying a strategical position in the administration and develop several procedures, the coordination was not successful in inserting the PB in the core of Political Admnistration. Regarding the format and dynamic of the Participatory Instance, it was noticed a simplification comparing to others expiriences, leading to a reduction in numbers of Participatory Instances and Rep´s which made difficult the process function. In the county PB was deliberated a restrict part of the total investiment, uncharacterizing and illegitimating these instances as they were the chiefly decision making location. The use of variable present on the literature with explination capacity for the process performance, allowed a better comprehension over the PB conclusions from 2003